Peran Komunikasi Organisasi Dalam Meningkatkan Kinerja Aparatur Sipil Negara(ASN) Pada Bagian Tata Pemerintahan Kota Makassar - Ainun Pratiwi , Nurul; Majid , Abdul; Idris , Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The objectives of this study are to identify what organizational communication efforts are being done to improve the performance of ASN in the Makassar City Governance section, and to find out how the role of organizational communication in improving ASN performance in the Makassar City Governance section is. The method used in this research is qualitative method. The type of research used is the field type (Field Research). This research lasted for one month and was located at the Makassar City Hall office with 4 informants. Based on the results of this study, it can be concluded that the efforts on the part of Governance in improving the performance of the State Civil Apparatus are by giving rewards and punishments, if the employee's performance is good, they will be rewarded, and if the employee's performance is not good, they will be punished. The role of communication carried out by the Makassar city government is vertical and horizontal communication, where superiors provide motivation to subordinates, and subordinates provide input or solutions to superiors and fellow employees in the governance section